Plasma free fatty acids and risk of heart failure: the Cardiovascular Health Study. - Djoussé, Luc; Benkeser, David; Arnold, Alice; Kizer, Jorge R; Zieman, Susan J; Lemaitre, Rozenn N; Tracy, Russell P; Gottdiener, John S; Mozaffarian, Dariush; Siscovick, David S; Mukamal, Kenneth J; Ix, Joachim H (Circ Heart Fail, 2013)
BACKGROUND: Although plasma free fatty acid (FFA) concentrations have been associated with lipotoxicity, apoptosis, and risk of diabetes mellitus and coronary heart disease, it is unclear whether FFA levels are associated with heart failure (HF). METHODS AND RESULTS: To test the hypothesis that plasma concentration of FFAs is positively associated with incident HF, we prospectively analyzed data on 4248 men and women free of HF at baseline and >65 years old from the Cardiovascular Health Study. FFA concentration was measured in duplicate by the Wako enzymatic method. Incident HF was validated by a centralized Events Committee. We used Cox proportional hazards to estimate the hazard ratio of HF per SD of FFAs. During a median follow-up of 10.5 years, a total of 1286 new cases of HF occurred. In a multivariable model adjusting for clinic site, comorbidity, demographic, anthropometric, and lifestyle factors, each SD (0.2 mEq/L) higher plasma FFA was associated with 12% (95% confidence interval, 6%-19%) higher risk of HF. Controlling for time-varying diabetes mellitus and coronary heart disease did not change the results (hazard ratio per SD, 1.16 [95% confidence interval, 1.09-1.23]). CONCLUSIONS: A single measure of plasma FFA obtained later in life is associated with a higher risk of HF in older adults. Additional studies are needed to explore biological mechanisms by which FFAs may influence the risk of HF and determine whether FFAs could serve as a novel pharmacological target for HF prevention.
Keywords: Aged; Aged, 80 and over; Biomarkers; Comorbidity; Fatty Acids, Nonesterified; Female; Heart Failure; Humans; Incidence; Kaplan-Meier Estimate; Linear Models; Male; Multivariate Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Time Factors; United States